2021
DOI: 10.3390/nano11051287
|View full text |Cite
|
Sign up to set email alerts
|

Combined Structural and Voltage Control of Giant Nonlinearities in Semiconductor Superlattices

Abstract: Recent studies have predicted a strong increase in high harmonic emission in unbiased semiconductor superlattices due to asymmetric current flow. In parallel, an external static bias has led to orders of magnitude control of high harmonics. Here, we study how this control can affect the operation of superlattice multipliers in a range of input frequencies and powers delivered by commercially available GHz sources. We show that the strongly nonlinear behavior can lead to a very complex scenario. Furthermore, it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 42 publications
(72 reference statements)
0
7
0
Order By: Relevance
“…Giant control of the harmonics through a combination of input power and voltage has been predicted in good agreement with experiments recently 18 . We also predict a strong control by manipulating interface scattering asymmetry 23 , as well as a more complex combination of input power and biasing voltage controls 24 .…”
Section: Methodsmentioning
confidence: 81%
See 3 more Smart Citations
“…Giant control of the harmonics through a combination of input power and voltage has been predicted in good agreement with experiments recently 18 . We also predict a strong control by manipulating interface scattering asymmetry 23 , as well as a more complex combination of input power and biasing voltage controls 24 .…”
Section: Methodsmentioning
confidence: 81%
“…Optimization is achieved in a joint effort combining predictive simulations and experiments. The output of the SSLMs is independent of the type of source used to generate input frequency, and both the THz source and heterodyne detection scheme are successfully described by a predictive simulation scheme, that is based on Nonequilibrium Green's Functions (NEGF) calculations and analytical solutions for the Boltzmann equation, as described in detail in the literature [18][19][20][21][22][23][24][25] . It is also possible to extract the relevant parameters from experimental current-voltage curves.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…There the resistance shows also logarithmic temperature dependences which may be attributed to an Altshuler–Aronov effect. Note that the effect can be further enhanced by interface roughness or superlattice design, as noted for the harmonic conversion efficiency in semiconductor superlattices [ 32 , 33 , 34 ] or in graphene chips [ 35 , 36 ]. However, further in-depth studies are required to properly determine the mechanisms for the observed effects and to ascertain the role of α-Sn and topologically inverted band structures for THz generation and photocurrents.…”
Section: Resultsmentioning
confidence: 99%